Maxillofacial Surgery and Craniofacial Deformity - Practices and Updates 2020
DOI: 10.5772/intechopen.89296
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maxillomandibular Advancement and Genioglossus Advancement on Sleep Quality

Abstract: Maxillomandibular advancement (MMA) using a standardized surgical procedure consisting of a LeFort I osteotomy and bilateral sagittal split ramus osteotomy and genioglossus advancement (GA) using a genioplasty improve airway volume, oxygen desaturation, and the AHI in patients with OSA. However, there are few reports on changes in sleep quality following MMA and GA. We assessed the effects of MMA and GA on sleep quality by comparing oxygen desaturation, AHI, and sleep architecture before and after surgery. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…18 With respect to orthognathic surgery for OSA, Sato et al published therapeutic outcomes for MMA plus GA in Japanese patients, revealing that mean AHI improved from 28.0 ± 24.6 events/h preoperatively to 7.4 ± 6.9 events/h postoperatively. 19 The tongue reportedly adapted to the enlarged oral space within 1 year after MMA, and the low preoperative position of the hyoid bone was thus improved. 20 Our results in the present study also showed that hyoid bone position contributes to the severity of OSA in patients with a long face type, suggesting that improving skeletal morphology by MMA and improving the position of the hyoid bone by GA may be effective for treating OSA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…18 With respect to orthognathic surgery for OSA, Sato et al published therapeutic outcomes for MMA plus GA in Japanese patients, revealing that mean AHI improved from 28.0 ± 24.6 events/h preoperatively to 7.4 ± 6.9 events/h postoperatively. 19 The tongue reportedly adapted to the enlarged oral space within 1 year after MMA, and the low preoperative position of the hyoid bone was thus improved. 20 Our results in the present study also showed that hyoid bone position contributes to the severity of OSA in patients with a long face type, suggesting that improving skeletal morphology by MMA and improving the position of the hyoid bone by GA may be effective for treating OSA.…”
Section: Discussionmentioning
confidence: 89%
“…For patients with tongue position issues, upper airway stimulation or genioglossus advancement (GA) is indicated 18 . With respect to orthognathic surgery for OSA, Sato et al published therapeutic outcomes for MMA plus GA in Japanese patients, revealing that mean AHI improved from 28.0 ± 24.6 events/h preoperatively to 7.4 ± 6.9 events/h postoperatively 19 . The tongue reportedly adapted to the enlarged oral space within 1 year after MMA, and the low preoperative position of the hyoid bone was thus improved 20 .…”
Section: Discussionmentioning
confidence: 99%